141 Face Time' for the First Time: Patients, Families and Junior Doctors. (16th March 2021) - White, H; Tuck, A; Pyrke, B; Murphy, E; Figg, K; Cartwright, G; Abdalla, B
Abstract: Introduction: Over the course of the COVID-19 pandemic, supporting effective communication between patients and their families has been a recognised challenge in the healthcare environment. Virtual communication via telecommunication and video-calling is more important than ever, but with minimal clinician education, preparation and relevant technological infrastructure available in the context of a global pandemic, we have recognised communication as an area for improvement as junior doctors working on a COVID-19 ward. Methods: We interviewed via telephone 22 nominated next of kin relatives of patients admitted to a COVID-19 ward in the University Hospital of Llandough during May 2020 using a pre-prepared survey. We then provided relatives with the opportunity to engage with video-call updates from a doctor (with the patient's permission). In appropriate scenarios, we used video calling to break bad news and to facilitate difficult communications with family members. These video calls were provided via Accurx, an NHS approved video communication system. Results: Initial survey results showed an average understanding score of their relative's current clinical plan of 5.5/10, with 63% of respondents saying they did not feel well informed. Nearly a quarter of respondents (22%) had received difficult news over the phone during the COVID-19 pandemic, and 86% said they would find video communication useful. Post-intervention survey results suggested a unanimous improvement in relative satisfaction, with relatives reporting an increased understanding around the admission, reassurance around the quality of care being given and less isolation from the patient. Conclusions: The COVID-19 pandemic has provided novel communication challenges to physicians, promoting flexibility and adaptation to some of the core inter-personal skills we develop throughout training. Technology plays a huge role in this, and the use of video calling in particular can preserve non-verbal communication within the doctor-relative relationship and improve emotional connection between patients and their loved ones.